Stock Market Volatility under Sanctions (International Journal of Management and Sustainability, 2014)
Since 1979, Iran has faced with unilateral and multilateral harsh sanctions due to its nuclear energy program. These sanctions have resulted in significant problem to both sanctioned and sanctioning parties. Given the fact that sanctions have had significant impacts on Iran’s economy and since Iran stock market is the barometer of its economy, it is assumed that sanctions affect the Iranian stock market as well. To test this hypothesis, this study studied the Iranian stock market volatility during harsh sanctions using ARCH models. The study found that, despite all sanctions, not only Iran’s stock market shows major stylized facts of any stock market’s volatility i.e. volatility clustering, fat tails and mean reversion but also it shows no irregularity which could be attributed to effect of sanctions. This finding was consistent with Iranian stock market regulators claiming Iranian stock market growth and the U.S. Congressional Research Service report 2013. Therefore, based on findings, this study concluded that Iranian stock market has not affected by sanctions.